The effectiveness of FEFA in teaching and learning foundations of applied mathematics / Ezzah Suraya Sarudin, Nor Alwani Omar and Syadatul Syaeda Mat Saleh - Sarudin, Ezzah Suraya; Omar, Nor Alwani; Mat Saleh, Syadatul Syaeda (UiTM Cawangan Perlis, 2020)
Memorizing formulas is one of the essentials tasks in learning activities. There are many formulas that have been constructed by previous researchers. The formulas developed have their own purpose such as to calculate, to estimate, to analyse and so on. One of the fields that involve more than a hundred formulas is in the education field. In education area, especially for mathematics subjects, students need to memorize the formula to let them easily get the answer to some of the questions given. In UiTM Perak Tapah Campus, there is one subject that requires students to memorize more than twenty formulas. The subject namely the Foundation of Applied Mathematics, which is taken by part three students in the Faculty of Applied Sciences. In previous semester, the failure rate for this subject is increasing and always be the top issue by top management. In this paper, the effectiveness of formula extracted from the given Appendix (FEFA) techniques is discussed. FEFA is one of the tools which will help students to reduce the total number in memorizing the formula. Primary data were gathered using the Quizizz application among 81 students who are taking MAT238 in the semester September-December 2019. The data was analysed by mixed design analysis to assess the effectiveness between pre-workshop and post-workshop. FEFA is found to be one of the good mechanisms to assist students in learning activities.